The Bemba-Banyamulenge case before the ICC: from individual to collective criminal responsibility - Ndahinda, Felix Mukwiza (International journal of transitional justice, 2013)
Jean-Pierre Bemba is on trial before the International Criminal Court (ICC) based on the legal theory of command responsibility for crimes allegedly committed by Congolese soldiers deployed in the Central African Republic (CAR) at the request of the country’s President Ange-Félix Patassé during the 2002-2003 conflict. Various ICC actors, including prosecutors, judges, witnesses, defense lawyers and victim representatives, have uncritically adopted the term ‘Banyamulenge,’ ordinarily an ethnonym for an eastern Congolese community, to refer to the purported perpetrators of these crimes. This article digs into the origins of the collective labeling of Bemba’s combatants in the CAR. It also examines the possible impact that negative narratives associated with Banyamulenge in the Bemba case may have on the already explosive identity politics in (eastern) Democratic Republic of Congo.